SPATIAL PRICE TRANSMISSION AND ASYMMETRIC ADJUSTMENT: THE CASE OF LOCAL AND IMPORTED RICE IN TOGO - Lanie, Tomgouani (L'Actualité économique)

(untitled) (HEC Montréal, 2020)
In this paper, we have investigated the extent and the speed of adjustment of six domestic markets of imported rice and the local market of processed rice in Togo to rice prices change on the global market and how the local market of paddy and the imported rice markets respond respectively to prices change in the processed rice and on the central market of imported rice Lomé and test for asymmetry in the adjustment process using both standard and threshold cointegration tests. Symmetric and asymmetric error correction models with respect to the linear and threshold cointegration relationships between markets pairings are estimated to investigate short-run prices dynamics.Results indicate that prices for the global to local markets pairings are cointegrated with relatively low price transmission elasticities. Prices on the imported rice markets in Togo are also cointegrated (when Lomé is considered as the central market). Threshold cointegration tests reveal that in the long-run, the local market of paddy adjusts asymmetrically to prices change in the processed rice and there is asymmetric adjustment of domestic markets of Cinkassé and Lomé to prices change on the global market. Except for Amégnran market, the four other domestic markets of imported rice adjust also asymmetrically to rice prices change on the central market of Lomé. In the short-run, there is asymmetric adjustment only between the global market and the imported rice markets of Lomé and Cinkassé. Among imported rice prices dynamics in Togo, only Cinkassé market adjust asymmetrically to prices change on the central market of Lomé. The results imply that oligopolistic middlemen in rice marketing in Togo are more sensitive and react quickly when rice prices change on the global market tends to squeeze their margins than changes that stretch them.